The Army of Prophet Muhammad and Pesantren Leaders’ Response to Religious Blasphemy in the Dutch East Indies Circa 1918-1919 - Nugroho, Setyo Adi; Rochmat, Saefur (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
At the beginning of the 20th century, Muslims in the Dutch East Indies encountered new challenges. This study aims to explore the movements of Muslims during this period, analyze the background of the establishment of the Army of Prophet Muhammad (TKNM), illustrate its developmental dynamics, trace the factors leading to its decline, and investigate the involvement of pesantren leaders in TKNM. Using the historical method proposed by Kuntowijoyo, this research reveals that the movements of Muslims at that time were influenced by the competition between modernist and traditionalist Islam. The establishment of TKNM was driven by conflicts between the putihan and abangan groups, the enthusiasm of Muslims, internal conflicts within the Sarekat Islam, disharmony between Islam and Javanese traditions, the veneration of H.O.S. Tjokroaminoto as the Ratu Adil, and the spread of Christianization, particularly following the publication of blasphemous articles against Prophet Muhammad SAW in Djawi Hisworo in January 1918. TKNM expanded with the formation of sub-committees in various regions, the broadening of its anti-Christianization campaign, and the active involvement of pesantren leaders. However, TKNM eventually declined as its direction became increasingly unclear.